Conformal Coating Surface Energy Calculation Based on Pelofsky Linear Relations - Piotr SZABLATA (Kalkulacja energii powierzchniowej dla lakierów ochronnych z użyciem relacji liniowych Pelofsky’ego, 2024)
In military, medical, and safety product manufacturing, the cost of every error is extremely high. The implementation of a conformal coating process carries significant risk if conducted without a proven method to check the compatibility of the lacquer and laminate specified in the product. This paper explains a method of material alignment verification based on Pelofsky relations. This straightforward solution allows engineers to evaluate the risk of potential issues with conformal coating protection at an early stage, before major investments are made in the expensive production process. Real-life production results are presented to support this thesis.
Keywords: Energia powierzchniowa lakierów ochronnych